Cardiac radioablation for atrial fibrillation: Target motion characterization and treatment delivery considerations. Issue 3 (21st January 2021) - Lydiard, Suzanne; Pontré, Beau; Lowe, Boris S.; Ball, Helen; Sasso, Giuseppe; Keall, Paul
Abstract : Purpose: The safe delivery of cardiac radioablation (CR) for atrial fibrillation (AF) is challenged by multi‐direction target motion, cardiac rate variability, target proximity to critical structures, and the importance of complete target dose coverage for therapeutic benefit. Careful selection of appropriate treatment procedures is therefore essential. This work characterizes AF cardiac radioablation target motion and target proximity to surrounding structures in both healthy and AF participants to guide optimal treatment technique and technology choice. Methods: Ten healthy participants and five participants with AF underwent MRI acquisition. Multi‐slice, cardiac‐gated, breath‐hold cines were acquired and interpolated to create three‐dimensional images for 18–30 cardiac phases. Treatment targets at the left and right pulmonary vein ostia (CTVLeft and CTVRight respectively) and adjacent cardiac structures were contoured and their displacements throughout the cardiac cycle were assessed. Target proximity to surrounding structures were measured. Free‐breathing real‐time two‐dimensional cine images were also acquired at 4 Hz frequency for between 1‐ and 2‐min duration. The motion of easily identifiable points within the target, diaphragm and sternum was measured to assess respiratory motion. Results: Target motion due to cardiac contraction was most prominent in the medial‐lateral direction and of 4–5 mm magnitude. CTVRight displacements were smaller in participants with AF than healthy participants in normal sinus rhythm. Nearby cardiac structures often moved with different magnitudes and motion trajectories. CTVLeft and/or CTVRight were in direct contact with the esophagus in 73% of participants. Target motion due to respiration was most prominent in the superior–inferior direction and of 13–14 mm magnitude in both healthy and AF participants. Conclusion: AF CR target motion and relative displacement was characterized. The combination of target motion magnitude and relative displacement to critical structures highlights the importance of personalizing motion compensation techniques for effective AF CR treatments. Abstract :